Exploring Character Education in 'Bocah-Bocah Borneo': Implications for Student Character Development - Monika, Marisa; Wati, Unik Ambar (STAI Hubbulwathan Duri, 2024)
Literature is an integral part of character formation efforts. This research aims to determine the contribution of the short story anthology book ‘Bocah-Bocah Borneo’ by Neneng Eliana to the character education of elementary school students. The research method used is inferential content analysis in the form of a process of describing, classifying, interpreting, and concluding the character values contained in the short story and implications for student character development based on Strengthening Ki Hajar Dewantara's Character Education. The data sources for content analysis included the short story anthology 'Bocah-Bocah Borneo', presidential regulations related to Strengthening Character Education inspired by Ki Hajar Dewantara's philosophy, and relevant articles from accredited scientific journals.